To the land of long lost friends - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series., 2019)
"In the latest book in the widely beloved No. 1 Ladies' Detective Agency series, Precious Ramotswe takes on a case for a childhood acquaintance but her inquiries will require an even more delicate touch than usual. Mma Ramotswe reconnects with an old friend who has been having problems with her daughter. Though Precious feels compelled to lend a hand, she discovers that getting involved in family affairs is always a delicate propositon. Mr. J.L.B. Matekoni finds himself embroiled in familial drama as well, when one of his clients asks for help evicting an unwanted houseguest who turns out to be the man's own brother. Elsewhere, Charlie and Fanwell are also involved in tricky matters of the heart, as Queenie-Queenie, Charlie's girlfriend, seems to have transferred her affections to Fanwell. It's up to Mma Makutsi to set things right, but she may be too distracted by her nemesis Violet Sephotho, who has somehow been appointed to the board of a charity. What is Violet up to now? As all of these mysteries are unraveled, Mma Ramotswe and the entire No. 1 Ladies' Detective Agency will be reminded of the value of tried-and-true wisdom--never judge a book by its cover"--